1995
DOI: 10.3139/217.950030
|View full text |Cite
|
Sign up to set email alerts
|

Solids Transport in Extruders

Abstract: A new analysis of the solids conveying of single screw extruders and solids feeders is developed. The new analysis is based on an assumption that the solids are pushed up the barrel by the flights on the screw. The new analysis when tested on literature data was found to be in qualitative agreement with all ratios of screw to barrel friction factor of the polymeric materials reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Tadmor et al [2,36,37] introduced an energy balance considering the heat conduction into the solid bed. Campbell and Dontula [38] as well as Hyun and Spalding [39] defined an angle for the solid bed pressing force, which was not normal to the active flight of the screw. Chung [40,41] presented a different approach assuming that the solid bed moves because of the presence of molten polymer films at the metal surfaces.…”
Section: Solid Conveying Sectionmentioning
confidence: 99%
“…Tadmor et al [2,36,37] introduced an energy balance considering the heat conduction into the solid bed. Campbell and Dontula [38] as well as Hyun and Spalding [39] defined an angle for the solid bed pressing force, which was not normal to the active flight of the screw. Chung [40,41] presented a different approach assuming that the solid bed moves because of the presence of molten polymer films at the metal surfaces.…”
Section: Solid Conveying Sectionmentioning
confidence: 99%
“…The models of solid conveying zone are based on the mechanism of dry friction represented usually by the classic approach of Darnell and Moll [1] with subsequent modifications, e.g. [2][3][4][5][6]. They were also extended to describe the solid conveying in grooved barrels in isothermal an non-isothermal cases.…”
Section: Weryfikacja Dooewiadczalna Komputerowego Modelu Procesu Uplamentioning
confidence: 99%
“…In 1991, Zhu et al 9 proposed a nonplug flow-type theory by treating the inner friction as a parameter. In 1992, Campbell et al 10 reported the importance of a screw helix in conveying solids, and in 1995, Campbell and Dontula 11 suggested new models assuming the additional normal force acting on the solids bed is the same as the frictional force between the barrel and the solids bed.…”
Section: Introductionmentioning
confidence: 98%